Fostering 21st-century communication: Students’ views on English club as a speaking platform - Suryanto, Suryanto; Rahayu, Desi; Shinjee, Bolormaa; Alsolami, Turki (Teaching English as a Foreign Language Journal, 2025)
In the contemporary globalized landscape, proficient communication in English is crucial for educational success and worldwide interaction. Despite extensive formal education, many Indonesian students struggle with speaking fluently in real-life contexts. English-speaking clubs (ESCs) have emerged as extracurricular platforms to help students overcome these challenges by providing a supportive, interactive environment for practicing speaking skills. Using a qualitative descriptive design, this research investigates the students' perceptions of the benefits and challenges of participating in an ESC at a high school in Yogyakarta, Indonesia. Through in-depth interviews with eight active club members, the research identifies several themes. The findings show the advantages of joining ESC, including increased speaking practice, improved language skills, enhanced fluency, and greater confidence. However, due to scheduling constraints, students also face challenges in joining ESC, such as fear of making mistakes, anxiety in spontaneous speaking situations, and limited participation time. The results of this study highlight the significance of building helpful, structured environments within ESCs to foster students’ communicative competence and self-assurance in English. This research provides a constructive understanding for teachers and administrators seeking to improve ESC programs and boost foreign language competence.